Isolation of an ABA Transporter-Like 1 Gene from Arachis hypogaea That Affects ABA Import and Reduces ABA Sensitivity in Arabidopsis - Ge, Kui; Liu, Xing; Li, Xiaoyun; Hu, Bo; Li, Ling (Frontiers in Plant Science, 2017)
Abscisic acid (ABA) transporters are essential for the transport of ABA from its sites of synthesis to its multiple sites of action within plants and are key players in plant stress responses. Despite their importance, there is limited information on ABA transporters in crop plants. In this study, we isolated and characterized an ABA transporter-like 1 (AhATL1) gene from peanut (Arachis hypogaea L.) whose cognate protein, AhATL1, is a member of the ATP-binding cassette transporter G subfamily and localizes to the plasma membrane. The expression of both the AhATL1 transcript and the corresponding protein were upregulated by water stress and treatment with exogenous ABA. Overexpression of AhATL1 in ecotype Columbia (Col) Arabidopsis (AhATL1-OX) plants reduced ABA sensitivity. When AhATL1-OX and Arabidopsis Col plants were subjected to drought stress, the expression of 9-cis-epoxycarotenoid dioxygenase 3 (AtNCED3) and responsive to desiccation 29 A (AtRD29A) accumulated rapidly in rosette leaves of both lines. In contrast, while expression of ATP-binding cassette G 40 (AtABCG40) was increased in Col rosette leaves, there was no change in expression of AtABCG40 in AhATL1-OX leaves. Similarly, water loss from detached leaves of AhATL1-OX plants was more rapid than from Col leaves. Therefore, we suggest that the function of AhATL1 is probably to modulate ABA sensitivity by specifically influencing ABA import into cells.